2019
DOI: 10.4038/slaj.v3i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of the foramen magnum in a Sri Lankan population

Abstract: Objective: The foramen magnum (FM) that transmits a large number of vital structures is an important anatomical landmark in neurosurgical procedures and forensic anthropology. The aim of the present study was to determine the dimensions and shape of the FM in a Sri Lankan population. Material and method: Forty-four adult skulls (32 males and 12 females) were selected for the study. Sagittal (FMSD) and transverse (FMTD) diameters of the FM were taken using a sliding digital vernier caliper to the nearest 0.01mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Similarly, 90% of calves and adults showed high titre at 2 weeks after the vaccination. According to previous studies, in the 6 th week, 50% of the animals showed over 1:4 antibody titres and 21% had over 1:8 CFT titres (Peiris, 1981). A slightly different scenario was observed in animals from abortion history negative farms; 37.5% of the animals showed over 1:4 and 18.75% had over 1:8 antibody titres in the study.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, 90% of calves and adults showed high titre at 2 weeks after the vaccination. According to previous studies, in the 6 th week, 50% of the animals showed over 1:4 antibody titres and 21% had over 1:8 CFT titres (Peiris, 1981). A slightly different scenario was observed in animals from abortion history negative farms; 37.5% of the animals showed over 1:4 and 18.75% had over 1:8 antibody titres in the study.…”
Section: Discussionmentioning
confidence: 52%
“…Once the president had agreed to the implementation of a pilot programme, the next challenge was financial. While the PTF technical committee had developed plans for a range of activities (Peiris & Nanayakkara, 2000), these plans had not been costed. No money had been set aside for redesigning classrooms to accommodate 'activity benches' and sinks and provision for running water.…”
Section: Financementioning
confidence: 99%
“…Sri Lanka is a tropical country, with monthly average temperature varying between 26°C and 33°C in the lowlands and 7°C and 21.6°C in the central highlands. The country is divided according to the amount, seasonality and variability of rainfall into three zones (wet, intermediate and dry zones) [9]. Only a few studies on vitamin D have been conducted in Sri Lanka and these are either restricted to one region or adult populations [10,11].…”
Section: Introductionmentioning
confidence: 99%